Flow-mediated dilation in athletes: influence of aging - Montero, D.; Padilla, J.; Diaz-Canestro, C.; Muris, D. M. J.; Pyke, K. E.; Obert, P.; Walther, G. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Controversy exists on whether endothelial function is enhanced in athletes. We sought to systematically review the literature and determine whether endothelial function, as assessed by flow-mediated dilation (FMD), is greater in athletes across all ages relative to that in their age-matched counterparts.